PENERAPAN METODE DRILL DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN - Fadhil Akbar (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
Application of the drill method in Islamic Religious Education learning which aims to improve students' ability to read the Al-Qur’an. The aim of this research is to find out about the application of the drill method in Islamic Religious Education learning starting from the implementation process, as well as supporting factors, inhibiting factors, and solutions for class XI P10 in improving their ability to read the Al-Qur’an in learning Islamic Religious Education at SMAN 1 Pare Kediri. This research uses qualitative methods with the type of descriptive. This research describes the actual situation regarding the application of the drill method in improving the ability to read the Al-Qur’an in Islamic Religious Education learning class XI P10 SMAN 1 Pare Kediri. This research uses observation, interview, documentation, and test data collection techniques. The results obtained from this research are the application of the drill method in improving the ability to read the Koran in Islamic Religious Education learning carried out with three main activities, namely: first, initial activities. Second, the core activity contains steps for learning Islamic Religious Education using the drill method. Third, closing activities.